The Effect of Internal Control System and the Implementation of Accrual-Based Government Accounting Standards on the Reporting Quality of Financial Statements in the Aceh Government Work Units - Elviza, Elviza; AR, Mulyadi; Yusuf, Yuslaidar; Quenzalo, Muliadi (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to examine the effect of the internal control system and the application of accrual-based government accounting standards on the quality of financial statements, both partially and simultaneously, in the Aceh Government Work Units. The population of this research was all 48 SKPAs (Aceh Work Units) in the Aceh Government. This research was conducted in the financial administration section of each SKPA in the Aceh Government work environment. The research selected the Financial Administration Officer (PPK) and Treasurer at each SKPA. The total sample size was 96 respondents. The data was processed using multiple regression analysis. The results showed that the internal control system (X1) and the application of accrual-based government accounting standards (X2) simultaneously affected the quality of financial statements, the internal control system (X1) partially affected the quality of financial statements and the application of accrual-based government accounting standards (X2) affected the quality of financial statements.